Impacto de la agresividad en el rendimiento académico en los alumnos de séptimos año de educación básica de la Escuela Ciudad de Quito del cantón Arenillas periodo lectivo 2012-2013. - Quito Cún, Sadia Aminda (2013)
First the theoretical framework was developed to support scientific research information. For this issues, concepts and definitions relating to aggression in order to know thoroughly the problem under study was investigated.